SISTEMATIZAÇÃO DA ASSISTÊNCIA DE ENFERMAGEM E PROCESSO DE ENFERMAGEM: DESENVOLVIMENTO DE UM GUIA PARA IMPLEMENTAÇÃO E AVALIAÇÃO - Almeida, Susana Lamara Pedras (2021)
Introduction: The Systematization of Care and the Nursing Process are themes of daily work and show quality and safe care for people who benefit from technical-scientific care. However, among the main difficulties in complying with the legislation in rela